The Evaluation of Hospital Social Responsibility Services in Gatot Soebroto Indonesia Central Army Hospital in 2015 – 2019 of Cleft Lip and Palate Patients - Widhani, Risandy Ditia; Jilvientasia; Utami, Gladya; Budiman; Guntoro; Irwansyah, Denny; Dessy, Anastasia; Surachman, A S; Adam, Harun (International Journal of Medical Science and Clinical Research Studies, 2022)
Background : Cleft lip and cleft palate are the most common congenital craniofacial anomalies treated by plastic surgeons. The incidence of cleft lip and palate is higher at lower socioeconomic levels. Hospital Social Responsibility (HSR) in Gatot Soebroto Central Army Hospital provides free cleft lip and palate surgeries to those who need it the most. The HSR services still need to be evaluated, to get an overview of epidemiologic profile of cleft lip and palate patients, and to improve the services itself. Materials and Method: The authors conducted a retrospective descriptive study based on online data of Smile Train HSR RSPAD Cleft Center from period of January 2015 to December 2019. All patients presented with cleft lip and/or palate were included. Results : Of all 713 patients in total; The gender distribution male 62.2% (444/713) was higher than female 37.7% (269/713). Most of the patients came from Java Island 77.5% (553/713). 685 were primary surgeries, 28 secondary surgeries. Among the primary surgeries, lip repair has the highest numbers 71.6% (491/685), followed by palate repair 27.2% (187/685), and alveolar bone grafting 1% (7/685). The most widely used surgical technique in lip surgery was the Millard 50% (345/685), while the most widely used surgical technique in palate surgery was the Bardach technique 22.9% (157/685). The median age for the primary lip repair patients was 1 year (range, 3 months to 60 years), and the median age for the primary palate repair patients was 4 year (range, 7 months to 26 years). Among secondary surgeries, lip revision with Millard technique was the highest (82.1%), followed by scar revision 3.57%, fistula repair (7.1%). The most common diagnosis was unilateral cleft lip (left 34.4%, right 13.2%) and followed by complete cleft palate (22.7%) Conclusion : Male patients were more dominant than females. The most common diagnosis was unilateral cleft lip. Incomplete diagnostic data and clinical photos of patients make it difficult to determine the complete diagnose of cleft lip and palate.